Subacute Thyroiditis Following SARS-CoV-2 Vaccines: Six Cases Report and Review of the Literature - Kurtulmus, Neslihan; Kayikci, Kubra (My University, 2022)
Subacute thyroiditis (SAT) is an inflammatory disease of the thyroid that develops following viral upper respiratory tract infections. SARS-CoV-2 virus, the cause of COVID-19, binds to the Angiotensin-Converting Enzyme-2 (ACE2) molecule expressed on the target cell surface. Thyroid gland shows high levels of ACE2 expression. The cases of SARS-CoV-2-related subacute thyroiditis and Graves- disease have been reported. It has recently been noted that vaccines for SARS-CoV-2 also induce autoimmune and inflammatory reactions. We present six (4 male, 2 female) cases of SAT that developed after mRNA and inactivated SARS-CoV-2 vaccines. And we have reviewed the literature. SAT was seen in 5 patients after mRNA vaccine, in one after inactivated vaccine. Their clinic and laboratory findings suggested to SAT. They were treated with nonsteroid anti-inflamatory drugs and/or methylprednisolone.They recovered within few weeks. Out patients did not have permanent hypothyroidism after SAT. The history of SARS-CoV-2 vaccination should be questioned in patients with subacute thyroiditis in pandemic days.